'Forlorn on the Fringe of Life': Exploring Working-Class Childhood in Katherine Mansfield's Short Stories. (12th January 2022) - Banerjee, Argha Kumar
Abstract: In Katherine Mansfield's short story 'Life of Ma Parker', the old, widowed charwoman is plagued by 'unbearable' thoughts of her deceased grandson Lennie: 'Why did he have to suffer so?' Lennie's unfortunate death in the story is not a solitary instance of tragic portrayal of working-class childhood in Mansfield's short fiction. In several of her tales she empathetically explores the marginalized existence of such children, occasionally juxtaposing their deplorable existence with their elite counterparts'. From social exclusion, child labour, parental rejection, infant and child mortality on the one hand to physical and verbal abuse, bullying in the school and appalling living conditions on the other; Mansfield's exploration of the working-class childhood in her short fiction is not only psychologically complex but sociologically significant. Focusing on the relevant short stories in her oeuvre, this brief analysis intends to closely examine such depictions of marginalized childhood experiences, particularly in light of the oppressive societal conditions that validate their repressive alienation and sufferings. Tracing various biographical circumstances that may have fostered Mansfield's deep empathy with the children's' predicament, this analysis also draws attention to her subtle oblique narrative strategies that effectively represent the plight of working-class children in a convincing and an ingeniously nuanced manner.